Nilai religiositas novel Suluh Rindu karya Habiburrahman El Shirazy: Kajian sosiologi sastra dan implementasinya sebagai bahan ajar sastra di SMA - Rettyaningsih, Maharani; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Universitas Mulawarman, 2024)
This research aims to describe the religious value in the novel Suluh Rindu by Habiburrahman El Shirazy and its implementation as literature learning material in high school. This type of research uses qualitative descriptive methods. The research data is in the form of quotations of words, phrases, clauses, and sentences containing religious value in the novel Suluh Rindu by Habiburrahman El Shirazy. This study's data source is the novel Suluh Rindu by Habiburrahman El Shirazy, designed with literary content analysis. Data collection techniques are reading, listening, taking notes, and documenting, and data validity using data triangulation. Data analysis techniques use dialectical methods. The results of this study show that the novel Suluh Rindu contains three religious values: creed, worship, and morals. The religious value of this novel can be implemented as literature learning material in high school based on reading and viewing elements with learning outcomes in the form of students being able to express ideas and views based on logical thinking principles from reading various types of texts (non-fiction and fiction) in print and electronic media. Students can appreciate fiction and non-fiction texts.